Hubungan Pengetahuan dengan Ketrampilan Mahasiswa Semester III tentang Asuhan Persalinan Normal di Akademi Kebidanan Harapan Ibu Pekalongan - Ana Setyowati; Swasti Artanti (Jurnal Kebidanan Harapan Ibu Pekalongan, 2026)
Childbirth is a physiological event that occurs naturally, but it can be accompanied by complications that endanger the lives of the mother and her baby, thus contributing to maternal and infant mortality. Providing normal delivery care is one of the basic knowledge and skills that must be mastered in carrying out one of the midwife's competencies. One of the competency standards for midwifery graduates is being able to provide normal delivery care according to the standards and authority of midwives. The research to be conducted includes research that uses an analytical observational study with a cross-sectional research design. The sampling technique uses quota sampling, namely sampling carried out by predetermining the sampling to be used. The data collection tool (instrument) used to obtain data is a document study method or a data collection method that is not directly aimed at the research subjects. The type of analysis in this study uses a chi-square test. The results obtained a p-value of 0.001, which can be concluded that there is a significant relationship between knowledge about delivery care and skills in providing normal delivery care for students.